Are the positions in the world ranking of competitive alpine skiers explainable by prominent polymorphisms in regulatory genes of mechanical and metabolic muscle functioning? - Gasser, B.; Frey, W. O.; Valdivieso, P.; Scherr, J.; Kopf, J.; Spörri, J.; Flück, M. (Research Quarterly for Exercise and Sport, 2025)
Background: The success of competitive alpine skiers with respective to their world ranking (WR) positions might be associated with prominent gene polymorphisms.